The policy of the International : a speech of and an interview with the Secretary of the International Camille Huysmans, member of the Belgian Parliament and the Brussels City Council. - Huysmans, Camille (London : Allen & Unwin, 1916)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Tweede Internationale (1889-1919).; vredesinitiatieven; Wereldoorlog 1